Answer:
Solve for the first variable in one of the equations, then substitute the result into the other equation.
Explanation:
Point Form:
![((2)/(3) ,-(5)/(3)) , (-1, -5)](https://img.qammunity.org/2023/formulas/mathematics/high-school/4x15aocp5cijvjgwkjwcynmd08bfgirfdf.png)
Equation Form:
x=
,
, y=
![-(5)/(3)](https://img.qammunity.org/2023/formulas/mathematics/college/nhbyn366g7k38pm7d6ss0z8z0nh22v38ux.png)
x = -1 , y =-5
Hope this answer your question... sorry I couldnt help more, if it didnt.